Bio Secrets of Coral Reefs Underneath the Shore - Nur Aifiah Binti Ibrahim Ibrahim (Journal of Marine and Coastal Science, 2026)
Coral reefs are highly complex marine ecosystems that support biodiversity, fisheries, coastal protection, and livelihoods, yet they are increasingly threatened by climate change, pollution, and human activities. This study investigates coral reef health using a mixed-methods approach that integrates socio-ecological perspectives with biophysical and spatial analyses. Semi-structured interviews with marine scientists, local stakeholders, and conservation practitioners documented perceptions of coral bleaching, reef degradation, restoration strategies, and governance. These insights were complemented by field observations and secondary data assessing coral structure, sediment composition, carbon sequestration, and the presence of radionuclides and heavy metals. Reef structural complexity was evaluated using rugosity indices and underwater photogrammetry, supported by spatial mapping of reef morphology and environmental conditions. Results confirm that reef health depends on tightly coupled biological and socio-economic processes, with degradation driven by climate stress, pollution, and human pressure. Human-mediated restoration, community-based conservation, and coordinated governance emerged as critical factors for enhancing reef resilience. The study highlights the need for integrated, multi-scale monitoring and management strategies to support sustainable coral reef conservation under accelerating environmental change.